INCREASING ACTIVITY AND PRACTICAL SKILLS THROUGH THE PROJECT BASED LEARNING MODEL - Nu’aimah, Sulasun; Wanarti Rusimamto, Puput; Joko, Joko; Novtiana, Rizcha; Arif Rosadi, Farchan (Universitas Muhammadiyah Makassar, 2024)
This research aims to explore increasing activeness and practical skills through the application of the Project Based Learning (PjBL) learning model. The research method used is qualitative with a descriptive analysis approach, with a focus on literature review. This research will explore literature related to the concept and implementation of PjBL in an educational context, as well as evaluate its impact on students' activeness in learning and development of practical skills. Through descriptive analysis, this research will examine various empirical studies, theories, and conceptual frameworks that support the effectiveness of PjBL in increasing students' active participation and development of practical skills. The focus of the research will also highlight aspects such as project management, collaboration between students, application of technology, as well as the role of teachers and the learning environment in supporting the implementation of PjBL. The results of this research are expected to provide a deeper understanding of the potential of PjBL in increasing student activity and developing practical skills , as well as providing practical guidance for educators to implement learning models that suit their respective contextual needs. It is hoped that the conclusions of this research can provide a significant contribution to the development of curriculum and learning practices that are more oriented towards student empowerment and contextual problem solving.